Teachers' Problems in Teaching Listening Comprehension at MA Patra Mandiri Plaju Palembang - Indah Wulandari; Amalia Hasanah; Deta Desvitasari (Didascein : Journal of English Education, 2024)
Of the four English skills, listening is the most important skill to be taught, and this process cannot be avoided by all teachers who teach English. However, some teachers still have problems teaching listening comprehension to students. This research aimed to discover the teachers’ problems in teaching listening comprehension at MA Patra Mandiri Plaju Palembang. Two participants were selected for this research. The researcher employed a purposeful sampling technique with a homogenous sampling teaching approach to choose the participants. The design of this study was qualitative research in the form of a case study. This study was conducted at MA Patra Mandiri Plaju Palembang; the researcher utilized one-on-one interviews through open-ended questions to collect data about the problems in teaching listening comprehension by following the interview guidelines. The data was analyzed by using a thematic analysis process. The results showed that there were some problems in teachers' teaching of listening comprehension at MA Patra Mandiri Plaju Palembang, which were divided into (a) students’ psychological factors (motivation, anxiety, and interest), (b) students’ background knowledge, (c) the attitude of students, (d) students’ lack of vocabulary, (e)teaching aids and media, (f) the material, (g) method of teaching listening, (h) fast speed of speech, (i) limited time.